Hydrogen production by sorption enhanced steam reforming (SESR) of biomass in a fluidised-bed reactor using combined multifunctional particles - Clough, Peter T.; Boot-Handford, Matthew E.; Zheng, Liya; Zhang, Zili; Fennell, Paul S. (MDPI, 2018)
The performance of combined CO2-sorbent/catalyst particles for sorption enhanced steam reforming (SESR), prepared via a simple mechanical mixing protocol, was studied using a spout-fluidised bed reactor capable of continuous solid fuel (biomass) feeding. The influence of particle size (300–500 and 710–1000 µm), CaO loading (60–100 wt %), Ni-loading (10–40 wt %) and presence of dicalcium silicate support (22.6 wt %) on SESR process performance were investigated. The combined particles were characterised by their density, porosity and CO2 carrying capacity with the analysis by thermogravimetric analysis (TGA), Brunauer-Emmett-Teller (BET), Barrett-Joyner-Halenda (BJH) and mercury intrusion porosimetry (MIP). All experiments were conducted with continuous oak biomass feeding at a rate of 0.9 g/min ± 10%, and the reactor was operated at 660 ± 5 °C, 1 atm and 20 ± 2 vol % steam which corresponds to a steam-to-carbon ratio of 1.2:1. Unsupported combined particles containing 21.0 wt % Ni and 79 wt % CaO were the best performing sorbent/catalyst particle screened in this study, when accounting for the cost of Ni and the improvement in H2 produced by high Ni content particles. SESR tests with these combined particles produced 61 mmol H2/gbiomass (122 g H2/kgbiomass) at a purity of 61 vol %. Significant coke formation within the feeding tube and on the surfaces of the particles was observed which was attributed to the low steam to carbon ratio utilised.
Keywords: Hydrogen; Sorption enhanced steam reforming; Combined multifunctional particles; Fluidised bed reactor; Biomass